Naphthalene diimide‐derivatives G‐quadruplex ligands induce cell proliferation inhibition, mild telomeric dysfunction and cell cycle perturbation in U251MG glioma cells. (24th September 2018) - Muoio, Daniela; Berardinelli, Francesco; Leone, Stefano; Coluzzi, Elisa; di Masi, Alessandra; Doria, Filippo; Freccero, Mauro; Sgura, Antonella; Folini, Marco; Antoccia, Antonio
Abstract : In the present paper, the biological effects of three different naphthalene diimides (NDIs) G‐quadruplex (G4) ligands (H‐NDI‐Tyr, H‐NDI‐NMe2, and tetra‐NDI‐NMe2) were comparatively evaluated to those exerted by RHPS4, a well‐characterized telomeric G4‐ligand, in an in vitro model of glioblastoma. Data indicated that NDIs were very effective in blocking cell proliferation at nanomolar concentrations, although displaying a lower specificity for telomere targeting compared to RHPS4. In addition, differently from RHPS4, NDIs failed to enhance the effect of ionizing radiation, thus suggesting that additional targets other than telomeres could be involved in the strong NDI‐mediated anti‐proliferative effects. In order to test telomeric off‐target action of NDIs, a panel of genes involved in tumor progression, DNA repair, telomere maintenance, and cell‐cycle regulation were evaluated at transcriptional and translational level. Specifically, the compounds were able to cause a marked reduction of TERT and BCL2 amounts as well as to favor the accumulation of proteins involved in cell cycle control. A detailed cytofluorimetric analysis of cell cycle progression by means of bromodeoxyuridine (BrdU) incorporation and staining of phospho‐histone H3 indicated that NDIs greatly reduce the progression through S‐phase and lead to G1 accumulation of BrdU‐positive cells. Taken together, these data indicated that, besides effects on telomeres and oncogenes such as Tert and Bcl2, nanomolar concentrations of NDIs determined a sustained block of cell proliferation by slowing down cell cycle progression during S‐phase. In conclusion, our data indicate that NDIs G4‐ligands are powerful antiproliferative agents, which act through mechanisms that ultimately lead to altered cell‐cycle control. Abstract : The effect of different telomeric G‐quadruplex (G4) ligands (three naphthalene diimides (NDIs) derivatives and RHPS4), were comparatively evaluated in radio‐resistant U251MG glioblastoma cells. Although displaying a lower than RHPS4 specificity for telomeric G4 and absence of radio‐sensitization potential, NDIs were very effective in blocking cell proliferation through the deregulation of proteins involved in cell‐cycle control and the slow‐down of cell‐cycle progression through the S phase.